A Propos the Historical Study of Reincarnate Lamas in Tibetan Societies: The Dalai Lama and the Emperor of China by P. Schwieger - Rheingans, Jim (Journal of religious history, 2021)
The Tibetan practice of recognising an individual as the conscious rebirth of a Buddhist saint has been a puzzling tradition to the outsider. Trülku literally refers to an earthly emanation body of a Buddha who manifests for the welfare of sentient beings. It is even more remarkable that the custom of recognising trülkus and institutionalising them through monastic estates is an innovation mainly found in the Tibetan cultural sphere. Peter Schwieger's The Dalai Lama and the Emperor of China: A Political History of the Tibetan Institution of Reincarnation (New York: Columbia University Press, 2015) is a substantial and necessary study, providing the first detailed exploration of the trülkü phenomenon as an institution from the perspective of political history. Focussing on the seventeenth to nineteenth centuries and the politics surrounding the institution of reincarnation between the office of the Dalai Lamas, the Chinese Qing emperors, and Mongol chieftains, it employs a vast number of previously underused sources such as legal and administrative documents. Reviewing Schwieger's study, this article discusses some other recent works about the trülku system and briefly reflects on the usage of sources for Tibetan history and the issue of researching the topic of reincarnation as such.